Identification of potential early regulators of aphid resistance in Medicago truncatula via transcription factor expression profiling - Gao, Ling-Ling (The New phytologist, 2010)
*Resistance to aphids has been identified in a number of plant species, yet the molecular mechanisms underlying aphid resistance remain largely unknown. *Using high-throughput quantitative real-time PCR technology, the transcription profiles of 752 putative Medicago truncatula transcription factor genes were analysed in a pair of susceptible and resistant closely related lines of M. truncatula following 6 and 12 h of bluegreen aphid (Acyrthosiphon kondoi) infestation. *Eighty-two transcription factor genes belonging to 30 transcription factor families were responsive to bluegreen aphid infestation. More transcription factor genes were responsive in the resistant interaction than in the susceptible interaction; of the 36 genes that were induced at 6 and/or 12 h, 32 were induced only in the resistant interaction. Bluegreen aphid-induced expression of a subset of these genes was correlated with the presence of AKR, a single dominant gene conferring resistance to bluegreen aphids. Similar transcription factor expression patterns of this subset were associated with bluegreen aphid resistance in other M. truncatula genetic backgrounds, as well as with resistance to pea aphid (Acyrthosiphon pisum). *Our results suggest that these transcription factors are among the early aphid-responsive genes in resistant plants, and may play important roles in resistance to multiple aphid species